2014
DOI: 10.1038/sc.2014.114
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract function in spinal cord-injured rats: midthoracic contusion versus transection

Abstract: Objectives: To compare changes in lower urinary tract (LUT) function with modifications in pathways that regulate LUT function using two different animal models (incomplete and complete) of spinal cord injury (SCI). Methods: Female Sprague-Dawley rats were used. SCI was made at Th8/9 by a contusion injury (contusion, n ¼ 9) or a complete transection (transection, n ¼ 9). Unoperated rats were used as normal controls (normal, n ¼ 6). LUT function was evaluated by micturition behavior in metabolic cages for 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…After SCI, the bladder is known to turn into a pathological state, as indicated by alterations in cystometric variables, such as the voided volume and detrusor pressure. 38 We would like to emphasize that these pathological changes in human urinary bladder function are among the most serious consequences of SCI, being associated with a substantially decreased quality of life and a high risk of mortality. 39,40 Therefore, the main goal of any pharmacological treatment in SCI is to improve cystometric characteristics towards the pre-SCI level.…”
Section: Real-life Data Examplementioning
confidence: 99%
“…After SCI, the bladder is known to turn into a pathological state, as indicated by alterations in cystometric variables, such as the voided volume and detrusor pressure. 38 We would like to emphasize that these pathological changes in human urinary bladder function are among the most serious consequences of SCI, being associated with a substantially decreased quality of life and a high risk of mortality. 39,40 Therefore, the main goal of any pharmacological treatment in SCI is to improve cystometric characteristics towards the pre-SCI level.…”
Section: Real-life Data Examplementioning
confidence: 99%
“…In the present study, the number of voids per day decreased and void size increased after transection at either level, which was consistent with other reports of urinary function after spinal injury. 31,32 The decrease in the number of daily voids could reflect any number of causes, including increased capacity due to bladder enlargement after SCI, enhanced urine retention due to an elevated threshold for voiding, and the inability to release urine due to EUS occlusion of the urethra during attempted voiding (i.e., DSD during non-voiding…”
Section: Urine Output Patterns and Individual Voids After Spinal Tranmentioning
confidence: 99%
“…A similar study including cSCI and tSCI models found that, while micturition pressure, non‐voiding contractions, bladder capacity and post‐void residual urine volumes differed from controls, there was no significant difference between the cSCI and tSCI groups. CGRP was significantly elevated in the dorsal horn in the SCI groups compared with the control group, but was not different between the SCI groups.…”
mentioning
confidence: 85%